Interactive effect between sleep and exercise on depressive symptoms in Chinese adolescents - Zou, Shoukang; Deng, Fang; Tan, Wenli; Fu, Yutong; Zhang, Hang; Xu, Hanmei; Tao, Yuanmei; Tang, Xian; Tang, Xiaowei; Xiong, Ping; Huang, Huiping; Huang, Ying; et al. (Frontiers in Psychiatry, 2023)
Objectives The study aimed to investigate the effects of sleep and exercise, individually and jointly, on depressive symptoms in Chinese adolescents. Methods Cluster sampling was used to conduct a cross-sectional, electronic survey among 11,563 students from five primary and high schools in Sichuan Province in Western China. The questionnaire contained custom-designed items concerning sleep and exercise, while it used the Center for Epidemiologic Studies Depression Scale to assess depressive symptoms and the Core Self-Evaluations Scale to assess core self-evaluation. Data were analyzed using descriptive statistics and multivariate linear regression. Results A total of 10,185 valid questionnaires were collected, corresponding to an effective response rate of 88.1%. Among the respondents in the final analysis, 5,555 (54.5%) were boys and 4,630 (45.5%) were girls, and the average age was 15.20 ± 1.72 years (range, 11–18 years). Only less than half of the respondents (4,914, 48.2%) reported insufficient sleep, while the remainder (5,271, 51.8%) had adequate sleep. Nearly one-quarter (2,250, 22.1%) reported insufficient exercise, while the remainder (7,935, 77.9%) reported adequate exercise. More than half of the respondents (5,681, 55.7%) were from vocational high school, 3,368 (33.1%) were from junior high school, 945 (9.3%) were from senior high school, and 191 (1.9%) were from primary school. The prevalence of depressive symptoms among all respondents was 29.5% (95% CI 28.7%−30.4%). When other variables were controlled, the depression score did not vary significantly with gender (B = −0.244, SE = 0.127, P = 0.054), but it decreased by 0.194 points per 1-year increase in age (B = −0.194, SE = 0.037, P < 0.001). Students getting adequate sleep had depression scores 2.614 points lower than those getting insufficient sleep (B = −2.614, SE = 0.577, P < 0.001), while students who engaged in adequate exercise had depression scores 1.779 points lower than those not exercising enough (B = −1.779, SE = 0.461, P < 0.001). The depression score decreased by 0.919 points per 1-point increase in the core self-evaluation score (B = −0.919, SE = 0.008, P < 0.001). In regression controlling for gender, age, and core self-evaluation, sleep and exercise were found to be related significantly to influence depressive symptoms (B = 0.821, SE = 0.315, P = 0.009). Conclusion Adequate sleep and adequate exercise are individually associated with milder depressive symptoms in Chinese adolescents. Our results further highlight the need for researchers and clinicians to take into account not only the individual but also the joint effects of sleep and exercise on depression in adolescents when conducting research and designing interventions. If sleep or physical exercise has substantially reduced the risk of depressive symptoms, further reductions by improving sleep and exercise become difficult and may even have opposite effects.